International Comparison of Self-Concept, Self-Perception and Lifestyle in Adolescents: A Systematic Review - Palenzuela-Luis, Natacha; Duarte-Clíments, Gonzalo; Gómez-Salgado, Juan; Rodríguez-Gómez, José Ángel; Sánchez-Gómez, Maria Begoña (International Journal of Public Health, 2022)
Introduction: Adolescence is considered a vital time to address healthy attitudes and values towards an effective transition to adulthood. The aim of this review was to analyse self-concept, self-perception, physical exercise, and lifestyle in the late adolescent population. Method: Systematic review of studies assessing the results by the Rosenberg Self-Esteem Scale, the General Health Questionnaire, the Activity Questionnaire for Adolescents, and the Health Behaviour in School-aged Children questionnaires in late adolescents. The PRISMA recommendations were followed. The CASPe quality-check system was applied, excluding articles with a score <8. Results: 1589 studies were found, and 69 articles were selected. Adolescents with high self-concept and self-perception tend to be emotionally stable, sociable, and responsible. No significant differences were found regarding self-concept and self-perception between different countries, but there were differences between men and women. Physical activity and healthy diet improve self-concept and perception of body image. Conclusions: Self-concept and self-perception are associated with responsibility, stability, and mental strength. Most healthy behaviours during adolescence are followed during adulthood. Socio-cultural level of Health Science students is a differential factor for overweight and obesity.